A comparison of L-dopa and clonidine growth hormone stimulation tests in children with short stature - Bolu , Semih; Asik , Abdulvahit (Annals of Medical Research, 2022)
Aim: The purpose of this study was to compare the results of L-dopa and clonidine GH stimulation tests in children with short stature and to identify which of these should be primarily selected.Materials and Methods: The records of 68 patients aged between 2.5 and 16.6 years presenting to the pediatric endocrinology clinic with short stature and undergoing GH stimulation tests between September 2016 and February 2021 were evaluated retrospectively. Cases with GH levels
Keywords: Clonidine; growth hormone stimulation test; L-dopa